2017
DOI: 10.5860/rusq.57.1.6435
|View full text |Cite
|
Sign up to set email alerts
|

For Your Enrichment: Developing a Reflective Practice Template for Citation Management Software Instruction

Abstract: One of the essential characteristics of successful librarians is the ability to use their experiences to build their skills. Donald Schön defined this concept as “reflectve practice” in his 1983 book The Reflective Practitioner. Here, Milewski and Williamson take on the role of reflective practitioners in examining their work in teaching citation management software. Their experience offers a model for librarians in all sorts of instructional positions to engage in reflective practice.—Editor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Podporu pro uživatele při využívání citačních manažerů často zajišťují referenční knihovníci a další zaměstnanci vědecké instituce. Řada z nich si ale není jistá svými kompetencemi pro práci s citačním manažerem (Childress, 2011;Milewski & Williamson, 2017). Podle Sarrafzadehové a Khaleghiho (2017) méně než polovina univerzit nabízí webové vzdělávací materiály a jen 33 % univerzit organizuje kurzy zaměřené na citační manažery, v obou případech se často omezují na jeden preferovaný nástroj (EndNote).…”
Section: Přehled Zdrojůunclassified
See 1 more Smart Citation
“…Podporu pro uživatele při využívání citačních manažerů často zajišťují referenční knihovníci a další zaměstnanci vědecké instituce. Řada z nich si ale není jistá svými kompetencemi pro práci s citačním manažerem (Childress, 2011;Milewski & Williamson, 2017). Podle Sarrafzadehové a Khaleghiho (2017) méně než polovina univerzit nabízí webové vzdělávací materiály a jen 33 % univerzit organizuje kurzy zaměřené na citační manažery, v obou případech se často omezují na jeden preferovaný nástroj (EndNote).…”
Section: Přehled Zdrojůunclassified
“…V případě podpory je nutné zvážit specifika různých kategorií uživatelů, protože jejich potřeby se liší například podle fáze studia (zejména ve smyslu žádoucích funkcí) nebo podle používaného hardwaru a softwaru (kompatibilita, rozhraní) (Milewski & Williamson, 2017). Tento článek může představovat východisko pro přípravu podpůrných materiálů i pro rozvoj kompetencí zaměstnanců univerzity, aby byli schopni pomoci při výběru a použití citačního manažeru podle potřeb konkrétního uživatele, nebo i pomůcku pro samotné uživatele při výběru citačního manažeru.…”
Section: Přehled Zdrojůunclassified
“…Students would also greatly benefit from referencing software training since research has shown that few of them use this type of software (Milewski & Williamson, 2017;Salem & Fehrmann, 2013). This would prevent them from making mistakes they often commit when referencing their sources according to norms (Mandernach, Zafonte, & Taylor, 2016), or when quoting and paraphrasing (Newton, 2016).…”
Section: Referencing Skills Definedmentioning
confidence: 99%
“…However, universities, whose mission is to develop skills, ethical values and integrity, (Gerstein & Friedman, 2016) are the perfect environment for students to learn about referencing. The mechanics of referencing could be dealt with by teaching students, as early as in their first year of university, how to use a bibliography management software, Endnote or Mendeley for example, which very few students know how to use according to Milewski and Williamson (2017). Teaching students to recognize the importance of sources, how to integrate them coherently in their assignments would certainly help them understand the relevance and value of writing with integrity (Grohe et al, 2013).…”
Section: Teaching Skills and Knowledge To Prevent Plagiarismmentioning
confidence: 99%
“…Pese a la necesidad de incorporar las Tecnologías de Información y Comunicaciones (TIC) en el proceso investigativo, específicamente en la gestión de la información científica, en Perú, Valles-Coral, Riascos-Armas y Hernandez-Torres (2020) reconocen la deficiente difusión del uso de referenciadores bibliográficos en la investigación; además Milewski y Williamson (2017) indican que su desconocimiento dificulta la gestión de citas y referencias bibliográficas, impidiendo dar valor agregado a la investigación por la necesidad de realizar este proceso de manera manual.…”
Section: Introductionunclassified